PERAN DAN STRATEGI KEPEMIMPINAN VISIONER DALAM MEWUJUDKAN MANAJEMEN KOPERASI SEKOLAH YANG EFEKTIF DAN EDUKATIF - Andini Salsa Fitriani; Khotimul Mubarok; Muhammad Syaroful Anam; Siswadi (STKIP Subang, 2026)
School management plays a crucial role in instilling independence and responsibility, yet often faces challenges in innovation and governance. This study aims to analyze the role and strategies of visionary leadership in realizing effective and educational school management. Visionary leadership is future-oriented through the formulation of a clear vision, the implementation of data-driven management, and the strengthening of organizational culture and the utilization of technology. The results indicate that visionary leadership can encourage the achievement of organizational goals while simultaneously shaping student character. Furthermore, student involvement in organizational activities helps develop critical thinking skills, collaboration, and independence. Therefore, the integration of managerial competencies and educational values ​​is key to creating an adaptive generation.